Penyajian Laporan Keuangan KPN SMPN XXX Padang Sesuai dengan Permenkop dan UKM Nomor 13 Tahun 2015 - Sartika, Dewi; Antonio, Beni (Universitas Dharma Andalas, 2025)
Abstract The presentation of financial reports in a financial institution is very important in describing the financial condition and performance of the financial institution. it can be imagined how if it does not have adequate financial reports, a financial institution may find it difficult to process transactions accurately, in detail, clearly, and structured. One of the microfinance institutions that still cannot present financial reports properly is savings and loan cooperatives, one of which is KPN SMPN XXX Padang. This is due to the limited ability of the management in presenting its financial statements. The purpose of this study is to present the financial statements of savings and loan cooperatives in accordance with the Regulation of the Minister of Cooperatives and SMEs Number 13 of 2015. Where in order to carry out management by cooperatives of savings and loan financing businesses that are carried out in an orderly manner in accounting so that they must apply the principles of accountability and transparency to produce financial reports that can be held accountable. The object of research is KPN SMPN XXX Padang. Data collection techniques used are interviews, observation, documentation and literature study. Data analysis used is data processing and data presentation. The results of the study of the presentation of financial statements in accordance with the Regulation of the Minister of Cooperatives and SMEs Number 13 of 2015 at KPN SMPN XXX Padang are: statement of results of operations, statement of changes in equity, balance sheet, cash flow statement, and notes to financial statements Abstrak Penyajian laporan keuangan dalam sebuah lembaga keuangan menjadi sangat penting dalam menggambarkan kondisi keuangan dan kinerja lembaga keuangan tersebut. dapat dibayangkan bagaimana jika tidak memiliki laporan keuangan yang memadai, sebuah lembaga keuangan mungkin sulit untuk memproses transaksi secara akurat, rinci, jelas, dan terstruktur. Salah satu lembaga keuangan mikro yang masih belum bisa menyajikan laporan keuangan dengan baik adalah koperasi simpan pinjam, salah satunya adalah KPN SMPN XXX Padang. Hal ini dikarenakan keterbatasan kemampuan pengurus dalam penyajian laporan keuangannya. Adapun tujuan dari penelitian ini adalah untuk menyajikan laporan keuangan koperasi simpan pinjam sesuai Peraturan Menteri Koperasi dan UKM Nomor 13 Tahun 2015. Dimana dalam rangka melakukan penyelengaraan oleh koperasi terhadap usaha pembiayaan simpan pinjam yang dilakukan secara tertib dalam akuntansi sehingga harus menerapkan prinsip akuntabilitas dan transparansi untuk menghasilkan laporan keuangan yang dapat di pertanggung jawabkan. Objek penelitian adalah KPN SMPN XXX Padang. Teknik pengumpulan data yang dilakukan adalah wawancara, observasi, dokumentasi dan studi kepustakaan. Analisis data yang digunakan adalah pengolahan data dan penyajian data. Hasil penelitian dari penyajian laporan keuangan sesuai dengan Peraturan Menteri Koperasi dan UKM Nomor 13 Tahun 2015 Pada KPN SMPN XXX Padang adalah: laporan perhitungan hasil usaha, laporan perubahan ekuitas, laporan neraca, laporan arus kas, dan catatan atas laporan keuangan